Amazonian tree mortality during the 1997 El Nino drought - Williamson, G. B.; Laurance, W. F.; Oliveira, A. A.; Delamonica, P.; Gascon, C.; Lovejoy, T. E.; Pohl, L. (Wiley-Blackwell, 2000)
In 1997, the Amazon Basin experienced an exceptionally severe El Nino drought. We assessed effects of this rare event on mortality rates of trees in intact rainforest based on data from permanent plots. Long-term (5- to 13-year) mortality rates averaged only 1.12% per year prior to the drought. During the drought year, annual mortality jumped to 1.91% but abruptly fell back to 1.23% in the year following El Nino. Trees dying during the drought dirt not differ significantly in site or species composition from those that died previously, and there was no detectable effect of soil texture on mortality rates. These results suggest that intact Amazonian rainforests are relatively resistant to severe El Nino events.